Kontekstualisasi hukum murtad dalam perspektif sejarah sosial hadis - Ja'Far Assagaf (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
Apostasy is a conversion of the original Muslim, abandoning the faith and following other religionthan Islam. In Islamic law, the perpetrator of apostasy will receive punishment of execution accordingto the jurists’ consensus. The consensus is understood from some hadiths containing the command toexecute the apostates and the fact of execution of apostates in the prophetic period of Muhammad saw.This article analyzes hadiths about the problematics of apostasy from the used terms, the background,and the contexts of the existance of command to execute apostates. The hadiths about apostasy wereanalyzed through socio-historical view of hadiths by the theory of compromise towards the seeminglycontradictive hadiths. The result of analysis shows that the background of execution of apostatestended to the war situation in that period and the social crimes committed by the apostates, indicated bythe existance of fact that the apostates committing religious crime, changing verses of al-Quran, receivedamnesty and were not executed. At present time, execution of apostates is a lively issue of debate. Theresult of analysis can provide other alternatives since apostate execution is not the only right way and itcannot be applied in any countries.